The F Street Mess : How Southern Senators Rewrote the Kansas-Nebraska Act - Malavasic, Alice Elizabeth (Book collections on Project MUSE., 2017)
"Malavasic argues that some Southern politicians in the 1850s did indeed hold an inordinate amount of power in the antebellum Congress and used it to foster the interests of slavery ... focuses her argument on Senators David Rice Atchison of Missouri, Andrew Pickens Butler of South Carolina, and Robert M.T. Hunter and James Murray Mason of Virginia, known by their contemporaries as the "F Street Mess" for the location of the house they shared. ... the F Street Mess was a functioning oligarchy within the U.S. Senate whose power was based on shared ideology, institutional seniority, and personal friendship"--